Climate change, food availability, and poverty: The case of Philippine rice - Cororaton, Caesar B. (Animo Repository, 2018)
The Philippines is experiencing the effects of wide swings in weather conditions in recent years. The country experienced super typhoons, floods, and extended periods of drought recurring in most of the regions. The agricultural commodity that is severely affected by climate change is rice, which is the staple food of Filipinos. Using a computable general equilibrium model calibrated to Philippine data, the paper analyzes the effects of climate change as it affects palay productivity. The analysis looks at the impact on palay production and rice supply, prices, consumption, household income, and welfare. The paper extends the analysis by computing the income distribution and poverty effects of the productivity changes by applying a poverty microsimulation using the 2012 Family Income and Expenditure Survey. The results indicate that climate change decreases palay production in rainfed (or non-irrigated) areas, leading to higher prices, reduced rice consumption, decreased real income of households, decreased welfare, increased income inequality, and poverty. These effects however are minimized or reversed if the limits imposed by the government on rice imports are relaxed. If the government reduces the trade barriers on imported rice which is considerably cheaper than domestically produced rice, supply of rice improves which decreases prices, rice consumption increases, real household improves, welfare increases, and income inequality and poverty decrease. © 2018 by De La Salle University.